NAT10 regulates p53 activation through acetylating p53 at K120 and ubiquitinating Mdm2 - Liu, Xiaofeng; Tan, Yuqin; Zhang, Chunfeng; Zhang, Ying; Zhang, Liangliang; Ren, Pengwei; Deng, Hongkui; Luo, Jianyuan; Ke, Yang; Du, Xiaojuan (EMBO reports, 2016)
As a genome guardian, p53 maintains genome stability by arresting cells for damage repair or inducing cell apoptosis to eliminate the damaged cells in stress response. Several nucleolar proteins stabilize p53 by interfering Mdm2–p53 interaction upon cellular stress, while other mechanisms by which nucleolar proteins activate p53 remain to be determined. Here, we identify NAT10 as a novel regulator for p53 activation. NAT10 acetylates p53 at K120 and stabilizes p53 by counteracting Mdm2 action. In addition, NAT10 promotes Mdm2 degradation with its intrinsic E3 ligase activity. After DNA damage, NAT10 translocates to nucleoplasm and activates p53‐mediated cell cycle control and apoptosis. Finally, NAT10 inhibits cell proliferation and expression of NAT10 decreases in human colorectal carcinomas. Thus, our data demonstrate that NAT10 plays a critical role in p53 activation via acetylating p53 and counteracting Mdm2 action, providing a novel pathway by which nucleolar protein activates p53 as a cellular stress sensor. Synopsis NAT10 acts as an E3 ligase for Mdm2 to promote Mdm2 degradation and stabilizes p53 under normal conditions. While under DNA damage conditions, NAT10 prevents Mdm2–p53 interaction by binding to p53 and acetylates p53, thus regulating p53‐mediated cell cycle arrest and apoptosis. NAT10 promotes Mdm2 ubiquitination and degradation with its E3 ligase activity under normal conditions. NAT10 acetylates p53 at K120. NAT10 translocates to nucleoplasm to bind and acetylate p53 at K120 upon cellular stress, thus contributing to p53 activation. Graphical Abstract NAT10 acts as an E3 ligase for Mdm2 to promote Mdm2 degradation and stabilizes p53 under normal conditions. While under DNA damage conditions, NAT10 prevents Mdm2–p53 interaction by binding to p53 and acetylates p53, thus regulating p53‐mediated cell cycle arrest and apoptosis.